1999
DOI: 10.1126/science.285.5436.2129
|View full text |Cite
|
Sign up to set email alerts
|

Affinity-Driven Peptide Selection of an NFAT Inhibitor More Selective Than Cyclosporin A

Abstract: The flow of information from calcium-mobilizing receptors to nuclear factor of activated T cells (NFAT)-dependent genes is critically dependent on interaction between the phosphatase calcineurin and the transcription factor NFAT. A high-affinity calcineurin-binding peptide was selected from combinatorial peptide libraries based on the calcineurin docking motif of NFAT. This peptide potently inhibited NFAT activation and NFAT-dependent expression of endogenous cytokine genes in T cells, without affecting the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
620
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 561 publications
(643 citation statements)
references
References 33 publications
21
620
1
1
Order By: Relevance
“…4B). In contrast, MIP1␣ mRNA expression was inhibited around 40 -50% by CsA at 6 and 12 h. The data are consistent with previous studies that showed the presence of functional NF-AT sites in the MIP1␣ promoter-enhancer region (47). Accordingly, these data suggest that AngII did enhance mRNA expression of both Th1-associated chemokines (IP-10 and MIP1␣), mainly via AT1 on MC, though their transcriptional regulation may be different.…”
Section: Angii-induced Chemotactic Activity Involves Can/nf-at and Nfsupporting
confidence: 91%
“…4B). In contrast, MIP1␣ mRNA expression was inhibited around 40 -50% by CsA at 6 and 12 h. The data are consistent with previous studies that showed the presence of functional NF-AT sites in the MIP1␣ promoter-enhancer region (47). Accordingly, these data suggest that AngII did enhance mRNA expression of both Th1-associated chemokines (IP-10 and MIP1␣), mainly via AT1 on MC, though their transcriptional regulation may be different.…”
Section: Angii-induced Chemotactic Activity Involves Can/nf-at and Nfsupporting
confidence: 91%
“…As shown in Figure 3A, we found that treatment of cells with either FK506 or cyclosporin A, two structurally unrelated, highly specific calcineurin inhibitors, both effectively attenuated the inhibitory effects of PGF2a on adipocyte differentiation, as determined by Oil Red O staining. Similarly, we found that the retroviral-mediated expression of VIVIT-GFP, a previously characterized specific calcineurin inhibitory peptide [Aramburu et al, 1999], also significantly rescued the inhibitory effects of PGF2a on adipocyte differentiation. The role of calcineurin in mediating the inhibitory effects of PGF2a on adipocyte differentiation was further confirmed by analyzing the expression of the late, mature adipocyte-specific marker gene, aP2.…”
Section: The Calcineurin Phosphatase Plays a Critical Role In Mediatisupporting
confidence: 66%
“…NCI3 might have fewer side effects than the commonly used immunosuppressive drugs CsA and FK506, because a compound blocking the calcineurin-NFAT signaling and not the general phosphatase activity of calcineurin is expected to have a lower toxicity [14,20]. However, it is unclear to what extent the toxicity of CsA and FK506 is due to inhibition of NFAT, to interference with dephosphorylation of other calcineurin substrates, to inhibition of the peptidyl-prolyl-cis/ trans-isomerase activity of the immunophilins, or to other non-calcineurin-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…The NFAT analogue VIVIT peptide was shown to bind efficiently to calcineurin [20]. We evaluated whether NCI3 inhibits this interaction by using FITC-labeled calcineurin, biotinylated 17mer VIVIT peptide and streptavidin-coupled microspheres.…”
Section: Nci3 Partially Interferes With the Calcineurin Vivit Peptidementioning
confidence: 99%